Описание выпуклых кривых - Лигун, А.А.; Шумейка, А.А. (Український математичний журнал, 2000)
Наведено опис опуклих кривих, який дозволяє звести задачу наближення опуклої кривої кусково-коловими лініями в метриці Хаусдорфа до задачі наближення 2 % -періодичних функцій тригонометричними сплайнами в рівномірній метриці. Наведено деякі властивості опуклих кривих. We present a description of convex curves, which enables one to reduce the problem of approximation of a convex curve by piecewise circular lines in the Hausdorff metric to the problem of approximation of 2π-periodic functions by trigonometric splines in the uniform metric. We describe certain properties of convex curves.